Will more Kelantan PAS elected representatives jump ship - New Sarawak, Tribune (New Sarawak Tribune, 2015)
KOTA BAHARU: The political atmosphere in Kelantan heated up a little following rumours that 10 PAS elected representatives in the state would jump ship and join Parti Amanah Ralcyat (Amanah) in January next year.